Measurement of the semileptonic branching ratio of B_{s};{0} to an orbitally excited D_{s};{**} state: Br(B_{s};{0}-->D_{s1};{-}(2536)mu;{+}nuX). - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2009)
In a data sample of approximately 1.3 fb;{-1} collected with the D0 detector between 2002 and 2006, the orbitally excited charm state D_{s1};{+/-}(2536) has been observed with a measured mass of 2535.7+/-0.6(stat)+/-0.5(syst) MeV/c;{2} via the decay mode B_{s};{0}-->D_{s1};{-}(2536)mu;{+}nu_{mu}X. A first measurement is made of the branching ratio product Br(b[over ]-->D_{s1};{-}(2536)mu;{+}nu_{mu}X)xBr(D_{s1};{-}-->D;{*-}K_{S};{0}). Assuming that D_{s1};{-}(2536) production in semileptonic decay is entirely from B_{s};{0}, an extraction of the semileptonic branching ratio Br(B_{s};{0}-->D_{s1};{-}(2536)mu;{+}nu_{mu}X) is made.